(untitled) (AYUSHDHARA, 2023)
Introduction: Osteoarthritis is a non-inflammatory heterogeneous group of degenerative joint disease. Homoeopathic remedy has encountered rheumatological problems very well. The main aim of this systemic review was to evaluate, specify and pinpoint the findings of all relevant individualised studies, thereby making the available evidence more accessible to decision-makers. Materials & Methods: An intensive search of RCT clinical research manuscripts published between 2000 and 2022 was done under various databases and it ensured that all papers belong to peer-reviewed journals. The data items were extracted by following points like publication years, population, interventions and comparator (Verum vs control), outcomes, methods, overall result and manufacturer of Verum. The five-point Jadad scoring system was used to assess the methodological quality of the selected trials with increasing scores indicating a higher quality. Whereas the null hypothesis in this systematic review was that individualized homoeopathic medicine had no impact. Results: A total of 56 experimental and controlled clinical trials were identified to be screened. After complete screening, the proper number of eligible papers was 12 and finally selected 08 RCT with a double-blind peer-review published paper. The studies maintain total number of patients of 1,891 and after dropping out 1,628 patients eagerly continued. The 08 studies focused on knee joints and lower back pain. Conclusion: In this study, we clearly understood that homoeopathic combination formulas work well on OA. Individualized Homoeopathic remedy was not effective due to insufficient trial reports. It’s also noticeable that homoeopathic combinations may have some adverse drug reactions. So, we need proper evidence for individualized homoeopathic medicine to say it works properly. It’s our duty to uptake trial testing continuously for the betterment of homoeopathy. However, more research is needed to completely evaluate and validate the efficacy or inadequacy of therapy with OA.